2006
DOI: 10.1080/10942910600596415
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Some Chemical and Biochemical Properties of Civil Cheese, a Traditional Turkish Cheese

Abstract: In this article, 15 randomly selected samples of Civil cheese, were purchased from different retail markets in the Erzurum province, Turkey and were investigated for some chemical and biochemical analyses. All cheese samples were analyzed for dry matter, fat, salt, ash, titrable acidity, total nitrogen, soluble nitrogen, ripening index, α s -and β-casein degradation, γ-casein, and peptides. Dry matter, fat, fat in dry matter, salt, salt in dry matter, ash, and acidity values in samples analyzed were found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
4
10
0
Order By: Relevance
“…Similar results were obtained for 60 d [12] or 180 d-old Civil cheeses [80]. No substantial degradation of nitrogen fractions was shown by gel electrophoresis of Civil [67,80]. It is fair to conclude from the data that hydrolysis of casein in Civil cheese is usually lower than in other brined varieties.…”
Section: Civil Cheesesupporting
confidence: 75%
See 3 more Smart Citations
“…Similar results were obtained for 60 d [12] or 180 d-old Civil cheeses [80]. No substantial degradation of nitrogen fractions was shown by gel electrophoresis of Civil [67,80]. It is fair to conclude from the data that hydrolysis of casein in Civil cheese is usually lower than in other brined varieties.…”
Section: Civil Cheesesupporting
confidence: 75%
“…After kneading, the body of curds is hung from a platform for stretching under its own weight and the stretching process is repeated until the curd has a smooth, plastic and fibrous texture. Following stretching, the cheese is cut into 12 cm pieces and brined in 9% NaCl brine for ripening [67,80]. The chemical composition of 15 samples of Civil cheese, determined by Sengul et al [67], was as follows (mean values): moisture, 63.9%; fat-in-dry matter, 5.81%; salt, 0.2%; titratable acidity, 1.3% and total nitrogen (TN), 4.4%.…”
Section: Civil Cheesementioning
confidence: 99%
See 2 more Smart Citations
“…1).The a s -CN, b-CN and, g-casein and other peptides fractions of Kes cheeses changed between 20.65-42.7, 22.95-41.85, and 21-56.4 %, respectively. The a s -CN ratio was reported to be 46.65% in Civil cheese [30] , 49.40% in Kulek cheese ripened for 90 days [31] and 41.58-56.49% in Feta cheese ripened for 120 days. [32] SDS-PAGE profile showed that neither a s -CN and b-CN were completely hydrolyzed in all Kes cheese samples (Fig.…”
Section: Nitrogen and Casein Fractionsmentioning
confidence: 97%